Twist angle-dependent transport properties of twisted bilayer graphene - Jin Hong Kim; Seoung-Hun Kang; Duhee Yoon; Hakseong Kim; Jin-Soo Kim; Mohd Musaib Haidari; Dong Jin Jang; Jin-Yong Ko; Young-Woo Son; Bae Ho Park; Jin Sik Choi (NPG Asia Materials)
Abstract Twisted bilayer graphene (tBLG) with small twist angles has attracted significant attention because of its unique electronic properties arising from the formation of a moiré superlattice. In this study, we systematically characterized the twist-angle-dependent electronic and transport properties of tBLG grown via chemical vapor deposition. This characterization included parameters such as the charge-neutral point voltage, carrier concentration, resistance, and mobility, covering a wide range of twist angles from 0° to 30°. We experimentally demonstrated that these parameters exhibited twist-angle-dependent moiré period trends, with high twist angles exceeding 9°, revealing more practically useful features, including improved mobilities compared to those of single-layer graphene. In addition, we demonstrated that the doping states and work functions were weakly dependent on the twist angles, as confirmed by additional first-principles calculations. This study provides valuable insights into the transport properties of tBLG and its potential for practical applications in the emerging field of twistronics.